Contribution of financial audit to good corporate governance - Yahia Djekidel; Ahmed Boudjelal; Benbertal Abdelkader (Dirassat Journal Economic Issue, 2021)
As a governance mechanism, the main objective of the external audit is to ensure the reliability of the financial information produced and disseminated by the entity and to prevent fraud and embezzlement that could harm that entity in the first place. The quality of the audit is usually understood by competence and independence. In order to ensure transparency in financial information and participate in the proper functioning of the entity, this article aims to study the contribution of financial auditing to good governance in order to reduce the information asymmetry between managers. of an entity and its shareholders and between managers and other stakeholders and thus to find a balance between the various bodies. This function can only be performed with a responsible, independent and technically competent auditor who complies with audit procedures and pursues quality training.